Dampak Mata Kuliah Akhlak Tasawuf Terhadap Disiplin Dan Akhlakul Karimah Mahasiswa - Rahmat Lutfi Guefara (STIKes Ibnu Sina Ajibarang, 2023)
A major challenge in education today is to enhance noble character among students, who have limited understanding and experience of Islam due to the low quality of Islamic education. The Sufism Ethics course taught to students has not been effective in cultivating noble character due to several factors, such as inadequate curriculum content, limited facilities, weak mastery of material and teaching methodology, and insufficient number and quality of educators. This study aims to analyze: the contribution of discipline in attending lectures to the development of noble character (akhlakul karimah) among students at STAI Panca Budi Trading, the contribution of the Sufism Ethics course to the development of noble character among students at the University of Quranic Science (Universitas Sains Alqur’an), and the combined contribution of both to the moral development of students at the University of Quranic Science. Using a quantitative method with primary and secondary data, data collection was conducted through questionnaires, documentation, and observation, and analyzed using simple regression and multiple linear regression. The results show that the Sufism Ethics course and discipline in attending lectures contribute significantly and positively to the development of good character among students at the University of Quranic Science.